Detection of soluble TRAIL in HBV infected patients and its clinical implications - Han, Li-Hui (World J Gastroenterol, 2002)
AIM: To detect the expression of soluble TRAIL (TNF-related apoptosis inducing ligand, TRAIL) in the peripheral blood of HBV infected patients and try to elucidate whether the expression level of sTRAIL have any correlativity with the clinical staging, the expression level of HBV markers and the degree of liver damage. METHODS: 52 cases of HBV infected patients were investigated, including 8 HBV carriers, 30 chronic hepatitis B, 11 cirrhotics and 3 HBV infection related hepatocellular carcinoma. Expression of soluble TRAIL and markers of the hepatitis B were mearsured by enzyme-linked immunosorbent assay. RESULTS: The expression level of sTRAIL in the peripheral blood of the HBV infected patients was significantly higher than that of healthy controls (1378.35 ± 540.23 pg/mL vs 613.75 ± 175.80 pg/mL, P < 0.001). In the group of chronic hepatitis, the expression level of sTRAIL was coincident with the status of the disease and was significantly correlated with the level of ALT. In the group of cirrhosis and liver cancer, its expression level was significantly higher than that of the healthy persons and HBV carriers, but lower than that of the hepatitis B patients; meanwhile, the expression of sTRAIL did not have any correlativity with the functional indexes of the liver. CONCLUSION: The soluble TRAIL in the HBV infected people may participate in the liver damage. Our results indicated that the expression level of soluble TRAIL may reflect the ravage of liver caused by host immune reaction to a certain degree.